2022
DOI: 10.3892/mmr.2022.12766
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of lncRNA USP2‑AS1 in the placentas of pregnant women with non‑diabetic fetal macrosomia promotes trophoblast cell proliferation

Abstract: Macrosomia is a common perinatal complication, with a series of adverse effects on newborns and pregnant women. However, the effects of long non-coding RNAs (lncRNAs) on non-diabetic fetal macrosomia (NDFMS) remain unclear. The aim of the present study was to investigate whether aberrant lncRNA expression in the placenta is involved in the pathogenesis of NDFMS and to elucidate its biological mechanisms. The expression profile of lncRNAs in the placentas of pregnant women with NDFMS was investigated using an A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“… 108 On the other hand, the effects of long non-coding RNAs (lncRNA) in non-diabetic foetal macrosomia have also been studied, suggesting that the lncRNA USP2-AS1 promotes placental development by affecting the proliferative activity of placental cells. 109 Moreover, another study indicated that lncRNA-SNX17 overexpression reduces the expression of miR-517a , which could play an important role in the regulation of birth weight, and increases the expression of IGF-1 in the human trophoblast cell line HTR-8/SVneo, thus enhancing the proliferation of HTR-8/SVneo. 110 It also reported that lncRNA-SNX17 could promote trophoblast proliferation through the miR-517a/IGF-1 pathway and could play a role in diabetic macrosomia placentation.…”
Section: The Effect Of Placental Changes On Foetal Anthropometric Mea...mentioning
confidence: 99%
“… 108 On the other hand, the effects of long non-coding RNAs (lncRNA) in non-diabetic foetal macrosomia have also been studied, suggesting that the lncRNA USP2-AS1 promotes placental development by affecting the proliferative activity of placental cells. 109 Moreover, another study indicated that lncRNA-SNX17 overexpression reduces the expression of miR-517a , which could play an important role in the regulation of birth weight, and increases the expression of IGF-1 in the human trophoblast cell line HTR-8/SVneo, thus enhancing the proliferation of HTR-8/SVneo. 110 It also reported that lncRNA-SNX17 could promote trophoblast proliferation through the miR-517a/IGF-1 pathway and could play a role in diabetic macrosomia placentation.…”
Section: The Effect Of Placental Changes On Foetal Anthropometric Mea...mentioning
confidence: 99%